Synchronous Surgical Management of Erectile Dysfunction and Stress Urinary Incontinence: A Systematic Review and Meta-Analysis of Reoperation Rates. (26th September 2022) - Pyrgidis, Nikolaos; Barham, David W.; Hammad, Muhammed; Sokolakis, Ioannis; Hatzichristodoulou, Georgios; Lentz, Aaron C.; Simhan, Jay; Yafi, Faysal A.; Gross, Martin S.
Abstract: Introduction: The efficacy, safety, and postoperative outcomes of synchronous surgery for concomitant erectile dysfunction (ED) and stress urinary incontinence (SUI) remain unclear. Objectives: We performed a systematic review and meta-analysis to evaluate the available synchronous surgical approaches for concomitant ED and SUI and to assess the reoperation rates compared to asynchronous surgery and surgery only for ED or SUI. Methods: We searched PubMed, Cochrane Library, and Embase databases until June 2022 for relevant studies. Based on data availability, we performed a meta-analysis of odds ratios (ORs) comparing reoperation rates after synchronous surgery in patients with concomitant ED and SUI versus asynchronous surgery, as well as surgery solely for ED or SUI (PROSPERO: CRD42022326941). Results: We included 18 studies in the systematic review (16, 517 patients) and 5 in the meta-analysis. Comparing synchronous implantation of penile prosthesis and artificial urinary sphincter (AUS) versus asynchronous surgery, no statistically significant differences were observed in the reoperation rates [OR:0.98, 95% confidence interval (CI): 0.52–1.84, I 2 :0%). Comparing synchronous implantation of both penile prosthesis and AUS versus implantation of only a penile prosthesis or an AUS, combined surgery was associated with higher reoperation rates (OR:2.02, 95%CI: 1.29–3.16, I 2 :36% and OR:1.7, 95%CI: 1.25–2.32, I 2 :0%, respectively). Synchronous surgery led to high satisfaction rates and significant improvement in ED and SUI. Evidence for the combination of penile prosthesis with a male sling or the ProACT device is low, but data suggests it may be safe and effective. The synchronous placement of a Mini-Jupette sling and penile prosthesis represents a promising treatment modality for the correction of ED and mild SUI and/or climacturia. Conclusions: Synchronous penile prosthesis and AUS implantation appears safe and effective in patients with severe ED and SUI. Further high-quality studies are mandatory to strengthen the current scarce evidence for synchronous surgery in patients with ED and SUI.